Randomised trial of ganciclovir and acyclovir in the treatment of herpes simplex dendritic keratitis: a multicentre study. Issue 2 (February 1996) - Hoh, H B; Hurley, C; Claoue, C; Viswalingham, M; Easty, D L; Goldschmidt, P; Collum, L M
Abstract : AIMS: This study was designed to assess the relative efficacy of topical ganciclovir 0.15% gel and acyclovir 3% ointment in the treatment of herpes simplex dendritic keratitis. METHODS: Both treatment modalities were administered on a five times daily basis to patients suffering from herpes simplex keratitis. Patients were assigned randomly to one of the two treatment groups for the purpose of the trial. They were then examined on days 2, 7, 10, and 14 to assess the rate of healing of the dendritic ulceration. RESULTS: There was no statistically significant difference detected in the rate of healing between the two treatment groups over the course of the trial. CONCLUSIONS: Review of the relative efficacy of topical ganciclovir and acyclovir in the treatment of herpes simplex dendritic keratitis showed that both treatment modalities were equally effective in their ability to heal the viral induced corneal ulceration. There were no significant side effects or adverse effects reported for either treatment modality.